Successful Treatment of Large Left Ventricular Thrombosis During Extracorporeal Membrane Oxygenation (ECMO): A Case Report and Review of the Literature - Xue‐ting Yang; Yi‐jin Chen; Han Zeng; Lei Deng; Li Chang; Yi Li; Meng‐long Song; Yang Zhang; Wei Peng; Dong Wang; Hua Jiang; Hong‐qiong Peng (Clinical Case Reports)
ABSTRACT We report a rare complication of left ventricular giant thrombus in a patient with fulminant myocarditis after venoarterial extracorporeal membrane oxygenation therapy. This case report offers simple anticoagulant treatment experiences to eliminate significant LV thrombosis in patient undergoing extracorporeal membrane oxygenation, so that patients do not need surgery.